Causes, Precautions and Management of Risk Factors Associated with Sports Injuries: Risk Factors Associated with Sports Injuries - Khan, Alamgir; Jamil, Muhammad; Butti, Shireen; Ahmad, Iftikhar; Ullah, Habib; Khan, Arsalan; Imtiaz, . (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Sports injuries are considered a global health problem that needs a special focus on public health to minimize the risk factors of sports injuries [1]. Sports Injuries refer to injuries commonly occurring during sports or exercise, but they are not only confined to sports. It can also appear in our routine life events. Suppose a factory worker can get tennis elbow injuries, and Painter gets shoulder injuries. Likewise, gardeners develop tendinitis even though they may not participate in sports [2]. The common sports injuries are sprains, strains, swollen muscles, shin splints, rotator cuff injuries, knee injuries, fractures, and dislocations. Based on nature, we can divide it into two types, i.e. intrinsic injuries and extrinsic injuries. Intrinsic injuries are those injuries which take place inside the body, while those injuries that take place outside the body are called outside injuries. Sports Injuries can occur in any part of the body, such as bones, joints, muscles, tendons, ligaments and cartilage [3]. Sports injuries may be categorized as chronic or acute sports injuries. Chronic or overuse injuries develop in sports where an athlete needs long-term repetitive motion, like long-distance running, cycling and swimming [4]. Chronic sports injuries include arthritis, tendonitis, tennis elbow, repetitive strain injury (RSI) and runner's knee [5]. Likewise, acute sports injuries consist of those injuries which happen suddenly. Wrist fractures. Ankle sprains. Shoulder dislocations are the best examples of acute sports injuries [5, 6]. In other words, those injuries which take place suddenly and need a short period of recovery are term as acute sports injuries, such as strain, sprain, dislocation and muscle aches etc. Similarly, those injuries that develop gradually and need more time for recovery are called chronic injuries [7]. Poor training, anatomical problems, muscle weakness, tendons, exercising ligaments, and unsafe environments are all causative factors of sports injuries [8]. In association with factors, sports injuries are usually instigated by overuse, direct impact, or the application of force greater than the body part can structurally withstand [9]. The main causes of injuries during sports are; lack of proper training, overtraining, long-term playing the same sports, playing on hard surfaces, and improper shoes and sports kits [2]. As a serious health concern, learning about preventive measures is important for athletes, coaches, and managers [10]. Preventive measures of sports injuries include; physical fitness, awareness about skills and techniques, and warm and cool down [11-13]. Due to injuries, a sportsman completely loses their performance. In addition, as a result of injuries, a sportsman feels soreness, swelling, muscular weakness, fatigue and pain. Along with physical problems, many psychological issues, such as fear, tension, lack of focus, and poor self-confidence, are also linked with sports injuries [14-18]. Different first aid techniques can help manage the severe effects of sports injuries, such as injury prevention, injury identification and treatment, and injury rehabilitation [19, 20]. Likewise, developing a fitness plan comprised of cardiovascular, strength and flexibility exercises, warm-up and cool down, staying hydrated, using proper equipment, etc. also used to manage sports injuries [21, 22]. There are five basic steps for preventing sports injuries among children. These preventive measures include wearing protective gear, i.e. helmets, protective pads, and other gear, warm up and cooling down, knowing the rules of the game, watch out for others and don't play when injured [22].